SOSIALISASI PENGENALAN EKONOMI ISLAM DI NAGARI TLUK KUALO INDERAPURA - Azhar, Azhar; Sarmigi, Elex; Nilda, Elvi; Yani, Ahmad (Institut Agama Islam Negeri Kerinci, 2023)
Every human being is ordered to work and strive in order to obtain a decent life. One effort that can be made is through economic activities. Economic activities themselves should be carried out by adhering to certain principles in order to achieve prosperity in life. Therefore, Islam as a perfect religion does not only pay attention to and teaches its followers to worship in totality, both vertically in relation to Allah, and horizontally to fellow humans. Humans are obliged to seek sustenance in a halal way. This service was carried out with the aim of introducing the Islamic economic system to the people of Nagari Tluk Kualo, Inderapura District. It is hoped that the results of this socialization will increase the understanding of the people of Nagari Tluk Kualo about Islamic economics.